Multiplicity of Positive Periodic Solutions of Singular Semipositone Third-Order Boundary Value Problems. (2nd January 2008) - Sun, Yigang
Abstract : We establish the existence of multiple positive solutions for a singular nonlinear third-order periodic boundary value problem. We are mainly interested in the semipositone case. The proof relies on a nonlinear alternative principle of Leray-Schauder, together with a truncation technique.